An association of periostin levels with the severity and chronicity of atopic dermatitis in children. Issue 6 (2nd August 2017) - Sung, Myongsoon; Lee, Kyung Suk; Ha, Eun Gyo; Lee, Seung Jin; Kim, Mi Ae; Lee, Seung Won; Jee, Hye Mi; Sheen, Youn Ho; Jung, Young Ho; Han, Man Yong
Abstract: Background: Serum periostin might be a biomarker in the pathogenesis of T helper 2‐type allergic diseases. The aim of this study was to investigate the relationship between serum periostin levels and the severity and chronicity of atopic dermatitis (AD) in children. Methods: This population‐based study examined 4076 children aged 4 to 13 years between June 2015 and July 2015. Of the 4076 children, 196—137 with a history of AD in the AD group and 59 without allergic diseases history in the healthy control (HC) group—were included for the final analysis. Results: Serum periostin levels were higher in the AD group than in the HC group ( P <.001) and were found to be positively associated with SCORAD score (Spearman's rho [ r ]=.24, P =.001). Children with AD‐onset time <2 years had significantly higher periostin levels ( P =.030) compared to those with AD‐onset time ≥2 years. The total eosinophil ( P =.189) and IgE levels ( P =.140) were comparable between children with AD‐onset time <2 years and those with AD‐onset time ≥2 years. After adjustment for age, gender, and parental allergic history, serum periostin level (OR: 1.03, 95% CI: 1.00‐1.06, P =.046) contributed to the development of AD in children with AD‐onset time <2 years. Conclusion: Serum periostin level may play a role in the severity and chronicity of AD in children.